2017
DOI: 10.1016/j.neuro.2017.07.027
|View full text |Cite
|
Sign up to set email alerts
|

Prenatal environmental chemical exposures and longitudinal patterns of child neurobehavior

Abstract: Background Prenatal chemical exposures may adversely affect neurodevelopment, but few studies have examined the persistence of these associations. We examined whether associations between prenatal bisphenol A (BPA) or polybrominated diphenyl ether (PBDE) exposures persist or resolve as children age. Methods We followed 346 mother-child pairs (enrolled 2003–2006) from Cincinnati, OH from pregnancy until children were 8 years old. We measured BPA in urine collected at 16 and 26 weeks gestation and PBDE-47 in s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
68
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 98 publications
(72 citation statements)
references
References 48 publications
3
68
1
Order By: Relevance
“…Even though all three studies utilized Wechsler scales to measure IQ, child IQ scores were evaluated at different ages (from 5 to 12 y). We may expect some variability in IQ measures by age, but a recent cohort study in Cincinnati, Ohio, reported rather high correlations of repeated IQ measures performed at [intraclass correlation coefficient (ICC) ranges 0.71–0.80 for performance, verbal, and full-scale IQ] ( Braun et al. 2017 ).…”
Section: Discussionmentioning
confidence: 99%
“…Even though all three studies utilized Wechsler scales to measure IQ, child IQ scores were evaluated at different ages (from 5 to 12 y). We may expect some variability in IQ measures by age, but a recent cohort study in Cincinnati, Ohio, reported rather high correlations of repeated IQ measures performed at [intraclass correlation coefficient (ICC) ranges 0.71–0.80 for performance, verbal, and full-scale IQ] ( Braun et al. 2017 ).…”
Section: Discussionmentioning
confidence: 99%
“…Over the last decade, a wide range of animal and epidemiologic studies have assessed the relationship between EDC exposure and health issues [ 15 , 16 , 17 , 18 , 19 , 20 ], and notwithstanding some instances of inconsistency or bias, this relationship has been repeatedly and convincingly confirmed. Thus, indeed, many diseases and disorders are now considered as being related to prenatal exposure to EDCs, such as fetal development disorders associated with low birth weight [ 21 , 22 ], prematurity [ 15 , 23 ], neurobehavioral disorders as autism and obsessive-compulsive disorders [ 24 , 25 ], loss of intelligence quotient points [ 26 ], allergies [ 27 ] pubescent development disorders [ 15 ] and congenital abnormalities [ 28 , 29 , 30 ]. Exposure to EDCs is also likely to cause breast cancers [ 31 ] and clear cell adenocarcinomas [ 32 , 33 , 34 ] in the offspring of exposed individuals.…”
Section: Introductionmentioning
confidence: 99%
“…In the past decade, human epidemiology has provided evidence for positive associations between pre-and postnatal exposure to certain chemicals, including known EDCs (e.g., PCBs, PBDEs, PFOS, bisphenol A, phthalates, paracetamol) and impaired neurodevelopmental outcomes in children. Data from birth cohorts have shown that chemical exposure during time periods that are critical for neurodevelopment can adversely impact cognitive functions (memory, language), attention, emotions, and social behaviors, partly with sexual dimorphic effects [4][5][6][7][8][9][10][11]. These observations are supported by experimental data in rodent models demonstrating persistent effects on behavior, cognition, and motor activity after exposure to EDCs during development, including PCBs, PBDEs, PFOS, bisphenol A, phthalates, and vinclozolin [12][13][14][15][16].…”
Section: Introductionmentioning
confidence: 89%